The Characteristics of Twin Building Facades in the Preservation of Heritage Areas - Mardhatillah, Wildha; HR, Ermywati; Jumriya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The intersection of Kajoetanganstraat–Semeroestraat–Riebeeckstraat, designed by Herman Thomas Karsten, features a distinctive and characteristic architectural design inherited from the colonial period. The buildings located at this intersection were originally designed to serve commercial functions, such as shopping complexes and hotels. Over time, the commercial character of the buildings along Semeru Street in particular has continued to develop, leading to increasing diversity in commercial building façade designs, which gradually may result in the deterioration of both the functional and physical conditions of these Dutch colonial buildings. Façade design plays a significant role in shaping the visual quality of the area. This study aims to identify and analyze the façade characteristics of the twin buildings in order to preserve them as architectural and cultural assets. The research method employed direct observation and photographic documentation of the twin buildings. The results of field observations and sketches were processed using design software to produce analyses and conservation concepts for the twin buildings through building preservation efforts.